Transforming higher education through Universal Design for Learning : an international perspective - Bracken, Sean (ed.); Bracken, Sean (ed.); Novak, Katie (ed.) (London Routledge, 2019)
"Providing insight into the background, theory and practical applications of Universal Design for Learning (UDL) in the Higher Education sector; this book examines and shares best practice in UDL implementation worldwide to provide institutions with strategies to increase accessibility and engagement. Every chapter provides a different perspective of how UDL has helped meet the needs of all students to ensure that education is accessible, culturally responsive, and socially just. Educational leaders and researchers across the globe assist in making this publication a crucial read for those who want to make a positive difference in Higher Education provision and outcomes"--
Includes bibliographic references and index.
Keywords: Inclusive education; Education, Higher